2017
DOI: 10.3847/1538-4357/aa9b30
|View full text |Cite
|
Sign up to set email alerts
|

Intracluster Patches of Baryons in the Core of the Fornax Cluster

Abstract: In the core of the Fornax cluster, on the West side of NGC 1399, we have detected a previously unknown region of intra-cluster light (ICL). It is made up by several faint (µ r 28 − 29 mag/arcsec 2 ) patches of diffuse light. The bulk of the ICL is located in between the three bright galaxies in the core, NGC 1387, NGC 1379 and NGC 1381, at 10 ≤ R ≤ 40 arcmin (∼ 58 − 230 kpc) from the central galaxy NGC 1399. We show that the ICL is the counterpart in the diffuse light of the known over-density in the populatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
117
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 70 publications
(132 citation statements)
references
References 49 publications
15
117
0
Order By: Relevance
“…As a related remark, some GCs (and any associated GC-LMXBs) might also be classified as part of the ICL. Indeed, Iodice et al (2017) found the aforementioned ICL to be spatially coincident with a previously known overdensity of blue GCs (D'Abrusco et al 2016).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…As a related remark, some GCs (and any associated GC-LMXBs) might also be classified as part of the ICL. Indeed, Iodice et al (2017) found the aforementioned ICL to be spatially coincident with a previously known overdensity of blue GCs (D'Abrusco et al 2016).…”
Section: Discussionmentioning
confidence: 70%
“…The third possibility is X-ray binaries associated with a more diffuse stellar population, either the extended stellar halo of NGC 1399 (Iodice et al 2016) or the ICL (Iodice et al 2017). The BCG halo grows primarily from mergers of infalling galaxies, whereas the ICL is built up mainly through stars tidally stripped from the outskirts of large galaxies or tidally disrupted low-mass galaxies orbiting in the cluster potential.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this light was shown to be the counterpart of previously detected over-densities of blue globular clusters (Bassino et al 2006;D'Abrusco et al 2016), indicators of a tidal stream. The morphology, the location and the faintness of this ICL were interpreted by Iodice et al (2017a) as signs of tidal stripping from the galaxies in this dense region, which would have passed close to the central cD in an earlier epoch. The velocity difference of FCC 170 with respect to NGC 1399 is compatible with tidal interactions with the cluster potential (Iodice et al 2017a), which could have strongly affected its evolution.…”
Section: Fcc 170: In the Core Of The Fornax Clustermentioning
confidence: 99%
“…The deep FDS imaging revealed that the region of the cluster where the clump is located hosts the bulk of the gravitational interactions between galaxies. It is the only region inside the virial radius where intra-cluster baryons were found, including faint stellar filaments between some of the galaxies (Iodice et al 2016(Iodice et al , 2017.…”
Section: Most Of the Intermediate Infallers (Region D Inmentioning
confidence: 99%